Study of Chemical Cleaning Technology in Compressed Natural Gas Water-Cooling System - Huang, Chang-Shan; Xu, Hui-Wu; Wu, Jin-Ying; Cheng, Yu-Shan; Chen, Min; Xue, Mian; Huang, Can (Asian Journal of Chemistry, 2014)
This paper is focused on the study of the chemical cleaning technology of the water-cooled piston compressor cooling system in compressed natural gas filling stations and the solution of practical problems such as equipment jams, high temperature, etc. The rotary coupon corrosion and weight loss methods corrosion inhibition properties of the cleaning agent and the electrochemical workstation and scanning electron microscopy (SEM) are used to investigate the electrochemical properties of the cleaner and the corrosion of the metal, respectively. Under proper cleaning conditions in the cleaning solution with the compound of 1-hydroxyethylidene-1,1-diphosphonic acid and urotropine, the descaling rate can reach 97.2 % and the corrosion rate of stainless steel and carbon steel are 0.0043 and 0.0784 g/m2 h, respectively. The potentiodynamic polarization curves show that the urotropine can reduce corrosion current and thus inhibit the corrosion of the metal. The SEM results reveal that the surface of the metal is complete and smooth after cleaning.